Fourth industrial revolution and higher education in the Kingdom of Saudi Arabia - Almutairi, Yousef Mubrik N.; Al-Saad, Atheer Farouk; Elmelegy, Reda Ibrahim; Bakr, Amany Abdel Hafez; Abdallah, Magdy Abdul Rahman; Almotairi, Khaled Mubark N. (Frontiers in Education, 2025)
This research is aimed at clarifying the effect of the industrial revolution on higher education institutions in the Kingdom of Saudi Arabia universities. This is accomplished by examining the Technology Acceptance Model (TAM) and Social Cognitive Theory (SCT) and acknowledging the relationship between content learning, learning opportunities, and instructional activities and the adoption of the industrial revolution. The research involved using a cross-sectional/descriptive and analytical method to analyze and investigate the effect of adopting the industrial revolution on university education institutions. In addition, it adopted a quantitative technique for analyzing the gathered data. A total of four hundred members of the academic staff were selected from the University of Hail (UoH) in Saudi Arabia. The results of the research revealed that there is a positive relationship between content learning, learning opportunities, content and instructional activities, and the adoption of the industrial revolution. Furthermore, there is a positive correlation between social impact and the fourth industrial revolution. The results confirmed that in order for the University of Hail to effectively respond to the challenges of the fourth industrial revolution and to prepare students for future jobs, the academic leaders must strive to improve the quality of teaching, learning, and research and make learning more relevant to the needs of the dynamic society.